Letter - Parker, Edwin H.
037-0081-001 ESTABLISHED 1873. TELEPHONE No. 21886. BRISTOL Trades & Labour Council OFFICE 1 BRISTOL BRIDGE, BRISTOL, 1. General Secretary: E.H. PARKER. All Communications for the Trades Council or Labour Party should be addressed to above. EHP/MLB 16th. July, 1937 The Secretary, National Joint Council, Transport House, Smith Square, LONDON. S.W.1 Dear Comrade, We are in receipt of your request for donations towards the shilling fund for the Spanish children, and I am asked to point out to you that Bristol has now taken 50 girls from Southampton, and have made themselves responsible, with the Lord Mayor of Bristol and Town representatives, to keep these girls for one year, at an estimated cost, all-in, of £2.000. To raise this amount we shall be obliged to reserve all contributions to the Spanish Fund for use in the locality. In fact, our appeals during the last fortnight, resulted in under £300 being subscribed, and it looks as though we shall have to use emergency measure in Bristol to raise the amount required. In the circumstances we have had to ask all Divisions, individuals and affiliated societies to reserve all contributions for the effort we are carrying out. Yours sincerely, Edwin H Parker Secretary. 292/946/37/81